Sacred Space and Cultural Symbol: Cultural Exegesis of Japanese Church Architecture - Antonius Firmansyah (Journal of Asian Orientation in Theology, 2019)
One of the many challenges of inculturation is cultural exegesis. Different cultures can have different understanding about the sacred expressed through their symbols. Church architecture is one of those symbolic expressions. Cultural symbols of church architecture can be interpreted merely as ornamental symbols of faith rather than an invitation for understanding the underlying context of religious experience within a particular culture. To avoid this, we need to find categories which can serve as methodological components for a proper cultural exegesis. This paper will attempt to apply three categories of nature, community, and cultural tradition as the standards to understand the sacrality of a cultural symbol. Through the application of these three categories into the architecture of Japanese church, we can find that cultural symbol embedded in church architecture serves more than as a bricolage expressing a symbolic identity of faith. Instead, it serves as a marker for cultural values being transformed through experiencing the sacred. Cultural symbols in church architecture is, thus, more about revealing the experience of divine transformation of a culture rather than its appropriation to the Christian faith.